Anthropometric indicators in identification of insulin resistance in elderly men - Pamella Cristine Anunciação; Rita de Cássia Lanes Ribeiro (O Mundo da Saúde)
Insulin resistance (IR) increases with advancing age, yet the underlying mechanism is not well established. Anthropometric and body composition indicators are alternative tools for assessing insulin resistance in a fast, non-invasive and inexpensive way. This study aimed to evaluate the association between anthropometric indicators and insulin resistance in older men. This cross-sectional study included 62 men aged between 60 and 92 years. We evaluated waist circumference (WC), sagit- tal abdominal diameter (SAD), body mass index (BMI), sagittal index (SI), conicity index (CI), body fat percentage (BF%), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR) and waist-to-thigh ratio (WTR). IR was determined by homeostasis model assessment (HOMA-IR). Statistical analysis consisted of correlation coefficient. All anthropometric indicators cor- related with HOMA-IR, highlighting the SAD (r = 0.680), BF% (r = 0.651) and WC (r = 0.591), which showed the highest correlations with the index. All measurements showed significant differences and progressive increase with increasing HOMA-IR. The differences between quartiles of HOMA-IR were even more pronounced for WC, SAD and BF%. BF% was a significant predictor for insulin resistance. Thus, obesity indicators correlated with the HOMA-IR index. We emphasize the stronger relationship between measures of central adiposity and insulin resistance, suggesting the usefulness of SAD in evaluating elderly subjects.